Output-Based Aid in Water : Lessons in Implementation from a Pilot in Paraguay - Dress, Franz (World Bank, Washington, DC, 2012)
Paraguay's aguateros-small private water companies-form an important part of the water sector, serving about 9 percent of the total population (or about 17 percent of those with piped water supply). But until recently they operated only in urban areas, where water resources are abundant and they could choose customers based on their ability to pay the full costs of providing service. A new World Bank-funded initiative seeks to attract aguateros and construction firms active in the water sector to unserved rural areas and small towns by providing an outputbased aid subsidy, awarded through competitive bidding. The initiative is the first attempt anywhere to apply this approach to rural and smalltown water sector investment. This Note reviews the early lessons.